Object-oriented perception: towards a contrastive approach to evidentiality in media discourse - Domínguez Romero, Elena (Kalbotyra, 2017)
This paper is a corpus-based study of the evidential realisations of object-oriented perception verbs in English and Spanish written and oral media discourse. The main aim of the study is to analyse and compare the different uses and complementation patterns taken by the English words look and sound and their Spanish counterparts se ve and suena. The procedure followed involves a contrastive analysis methodology: (i) description of data, (ii) juxtaposition and (iii) contrast. The data has been taken from oral and written media discourse corpora in English and Spanish. The study has revealed interesting similarities and differences in the uses and complementation patterns adopted by object-oriented perception verbs in both written and oral English and Spanish, thus making a contribution to a debate in which Spanish has been obviated to date.